Respuesta :
Answer:
3. g(x) > h(x) for x = -1
5. For positive values of x, g(x) > h(x).
6. For negative values of x, g(x) > h(x).
Step-by-step explanation:
We have the functions, [tex]g(x) = x^2[/tex] and [tex]h(x) = -x^2[/tex].
From the graph plotted below, we see that,
For positive values of x, g(x) > h(x).
For negative values of x, g(x) > h(x).
Moreover, we have,
[tex]g(x) = x^2[/tex] [tex]h(x) = -x^2[/tex].
x= -1 g(x)= 1 h(x)= -1
x= 3 g(x)= 9 h(x)= -9
So, we get, g(x) > h(x) for x = -1 holds.
Thus, the options that are correct are 3, 5 and 6.